Meanings of a Territorial Infrastructure: the Airports - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2011)
The paper want to explore the major meanings of an airport. It is a territorial infrastructure that increases the spatial accessibility and the economic potential of a territory; in this sense, it is also a port to boost tourism and cultural exchanges. It is also an infrastructure bringing with it investment in other areas of mobility. Since the sixties, finally, it has also become an architectural icon and a symbol of urban level. Objective limitations remain; in particular for the position, outside the city, and for the service, that can be ordered and tidy. The airports have an important role for the move of people. As the international transport statistics the number of passengers in the main airports is growing, also if has suffered the blows of the international economic crisis. The expansion of air passenger traffic is related with the tendency to the specialization of travels, according to the range of movement of persons. The actual changing economic world coincides with a process of continuous growth of passenger flows, partly independent from that of economic growth; the combination of these two processes has multiplied the number of connections and has produced new phenomena. The transport system isn’t a neutral system, also if it is sectorial; it, rather, is linked very strongly with the territorial system in which it operates and with the location choices of firms and individuals. This reflection has value for all the transport’s infrastructures, although with different degrees. In this ranking the airports are located in a great importance position, as they can be a strategic asset in the territorial economic growth processes, contributing directly or indirectly to the development of local enterprises. An airport operates whether as a supplier of infrastructure or as a business reality in itself, operating in a highly competitive market with an high speed of change. Airports are an architectural and urban typology typically lacking of physical and spatial integration with their urban context; for this the airports have evolved into semi-autonomous spaces. For their dimensional characteristics and for the incidence of pollutants factors, must be placed outside the city, often at significant distances from the same: their fundamental role in the urban structure is expressed, therefore, in external spaces from the city. As defined above, the airport is an urban infrastructure. But it is other things also: it is an ordered place, because its management requires defined actions and sequences of activities that are the true opposite of the urban disorder. Both the structures are complexes but the airport is a side where the hierarchical roles are well defined, more than in other sides, and it is the side where the authority is recognized and well accepted. The building of new airports, or the modernization of existing structures are a sign of the sectors’ vitality and of the necessity to offer better services to an expanding custom. But the airports have created a lot of imagines around their presence and use. mplessi, ma il primo è uno spazio in cui i ruoli gerarchici sono ben definiti e dove è l’autorità è riconosciuta e ben accettata. La costruzione di nuovi aeroporti, o l’ammodernamento delle strutture esistenti, è un segno della vitalità del settore e della necessità di offrire migliori servizi ad una utenza in espansione.